2014
DOI: 10.1007/s13277-014-2755-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miRNAs in non-small-cell lung carcinomas and their association with clinicopathological features

Abstract: Lung cancer is recognized as a leading cause of cancer-related deaths worldwide. Over the past several years, evidence emerged that microRNAs (miRNAs), a class of small non-coding RNA molecules regulating gene expression at posttranscriptional level, play an important role in cell functioning, as well as in human diseases. Here, we analyzed expression of miR-15a/16, miR-21, miR-34a, miR-126, miR-128, and miR-210 at transcriptional level in 30 non-small-cell lung carcinoma (NSCLC) tumor tissues compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 66 publications
0
24
1
Order By: Relevance
“…Statistical significance was accepted at a value of P < 0.05. The relative gene analyses of the study groups were performed using the REST 2009 (Relative Expression Software Tool program Qiagen â [30]), in accordance with the literature (Leduc et al 2011;Salis et al 2014;Tafsiri et al 2015). The statistical significance was accepted at a value of P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance was accepted at a value of P < 0.05. The relative gene analyses of the study groups were performed using the REST 2009 (Relative Expression Software Tool program Qiagen â [30]), in accordance with the literature (Leduc et al 2011;Salis et al 2014;Tafsiri et al 2015). The statistical significance was accepted at a value of P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are a class of short (19)(20)(21)(22)(23)(24) nucleotides in length) endogenous non-protein-coding single-stranded RNAs, which regulate ~1/3 of mRNAs in the human genome (18). miRNAs regulate mRNA expression by binding the 3' untranslated regions (3'UTRs) of target mRNAs and inducing either translational repression or transcript degradation (19).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that miRNAs contribute to various physiological and pathological processes, including cell proliferation, differentiation, morphogenesis, cell cycle regulation, apoptosis, migration and invasion (20). miRNAs are classified as tumor-suppressive miRNAs and oncogenic miRNAs (21). Tumor suppressive miRNAs are downregulated in cancer and inhibit carcinogenesis and progression, whereas oncogenic miRNAs are upregulated in cancer, and enhance the initiation and development of cancer (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al and Ye et al showed that miR-138 could inhibit NSCLC cell growth and tumour growth in nude mice by suppressing the expression of its target genes the enhancer of zeste homolog 2 (EZH2) and 3-phosphoinositide-dependent protein kinase-1 (PDK1) [16,19]. In general, however, one miRNA has numerous target genes, and a miRNA may be multifunctional, which means that miR-138 may inhibit NSCLC cell growth by targeting some other genes associated with the EMT of NSCLC [5,7,17,21,22].…”
Section: Introductionmentioning
confidence: 99%